(3QSGdI aj eSCdI CUhdjIs - (3eMeO Hf Rjf GdOjf gdGd GdMfaj,J (B1012 (3g` s
(3ChdgG (B:s
(3Wdb GdKGfi KdGKkG bHd GdONhd aJRhLJ HKGdK s
(3BNQgG (B:s
(3hdFf SCdJge ef Ndb GdSehGJ hGdCQV djbhdf Ndbgf GdYdje aGfg Chdi HGdLhGH hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3CUhd abgs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs